2019
DOI: 10.1029/2018ja026280
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Topside Ionospheric Vertical Scale Height Based on Ionospheric Radio Occultation Measurements

Abstract: An artificial neural network (ANN) method for the modeling of global topside ionospheric vertical scale height (VSH) using electron density profiles retrieved from Global Navigation Satellite Systems radio occultation (RO) data is proposed in this study. The data for this study are 80,124 VSHs derived from the events randomly selected from 9 years of Constellation Observing System for Meteorology, Ionosphere, and Climate RO measurements and 144,530 VSHs derived from the events randomly selected from 16 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
(58 reference statements)
1
10
0
Order By: Relevance
“…From this regression we obtain VSH values of 205 km on the dayside (6 ≤ MLT < 18) and 167 km on the nightside (MLT < 6 and MLT ≥ 18). These scale heights are within the range of typical estimates at geodetic altitudes of 350-500 km (e.g., Figure 2 in Hu et al, 2019 andFigure 1b in Stankov &Jakowski, 2006).…”
Section: Appendix A: Correction and Adjustment Of Nesupporting
confidence: 83%
See 1 more Smart Citation
“…From this regression we obtain VSH values of 205 km on the dayside (6 ≤ MLT < 18) and 167 km on the nightside (MLT < 6 and MLT ≥ 18). These scale heights are within the range of typical estimates at geodetic altitudes of 350-500 km (e.g., Figure 2 in Hu et al, 2019 andFigure 1b in Stankov &Jakowski, 2006).…”
Section: Appendix A: Correction and Adjustment Of Nesupporting
confidence: 83%
“…From 380 conjunctions between Swarm B and either Swarm A or Swarm C for which Swarm LP data are currently available (December 2013 through February 2020), we derive the Vertical Scale Height VSH ≡ dh∕(d ln N e ) (e.g., Hu et al, 2019). We use "robust regression" (e.g., Holland & Welsch, 1977;Huber, 1973) to estimate VSH from the ratio of plasma density measurements during the 380 identified conjunctions ( Figure S2c in supporting information).…”
Section: Appendix A: Correction and Adjustment Of Nementioning
confidence: 99%
“…Additionally, the value of the month variable is decimal with the value range of from 0.0 (on 1 January) to 12.0 (on 31 December). The example for the four new variables (i.e., NmF2, hmF2, VSH, and r) are shown in Figure 1 of Hu et al ().…”
Section: Methodsmentioning
confidence: 99%
“…The procedure used this study follows that of Hu et al (), which is shown in the flowchart in Figure , the blue cylinders denote the databases used in this study, white rectangles are the procedure steps, and the parallelograms are the dependent variable set. In this study, part of the independent variables, LT, month, altitude, and the Ne profile are extracted from the ISR data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation